Pengaruh Good Corporate Governance, Profitabilitas, dan Ukuran Perusahaan terhadap Nilai Perusahaan - Kholifia Alzhafy; Aulia Syafira Azzahro; Nadia Martha Nurfaizah; Irma Ayu Amalia; Ibrahim Ibrahim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The primary focus of this research is to evaluate the influence of Good Corporate Governance (GCG), profitability levels, and entity scale on the market value of coal mining companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. This study adopts a quantitative design by utilizing secondary data from the official IDX website, where 8 companies were selected as samples from a total population of 34 coal sub-sector companies through purposive sampling techniques. Data processing was carried out through panel data regression analysis using Eviews 12 software. The research data indicates that, independently, the implementation of good corporate governance and the level of profit acquisition do not contribute significantly to determining the value of the entity. Conversely, company size is proven to have a significant negative impact. Simultaneous testing confirms that these three independent variables collectively have a significant effect on company value. These findings indicate the need for strategies that consider factors beyond good corporate governance and profitability in efforts to increase company value, such as operational efficiency and proper asset management.